Effect of Bentonite on the Pelleting Properties of Iron Concentrate - Hao Liu; Bing Xie; Yue-lin Qin (Journal of Chemistry)
The physical and chemical properties such as particle size, montmorillonite content, swelling degree, water absorption, and blue absorption of A, B, and C bentonites were studied under laboratory conditions. The effects of adding different quality and different proportion of bentonite on falling strength, compression strength, and shock temperature of green pellet were investigated. The experimental results show that the montmorillonite content, water absorption, and methylene blue absorption of bentonite-B are the highest. And the quality of bentonite-B is the best, followed by bentonite-C and bentonite-A poor quality. When the amount of bentonite-B reduced from 1.5% to 1.0%, the strength of green pellets and the shock temperature both decrease. As the same proportion of A, B, and C bentonites, the green-ball strength and shock temperature are as follows: bentonite-A > bentonite-B > bentonite-C.